Küreselleşme sürecinde Türkiye’de sivil toplum ve demokratikleşme - Kaplangil, Diren (My University, 2010)
Küreselleşmenin nasıl bir sivil toplum ve demokrasi anlayışı getirdiği ve bunun Türkiye'yi ne şekilde etkilediği konusuna dair bu çalışma, öncelikle sivil toplum ve demokrasi ilişkisini küresel düzlemde ele almakta, bu bağlamda Türkiye'ye özgü sivil toplum ve demokratikleşme perspektifini ortaya koymayı amaçlamaktadır. Bugünkü uluslararası ilişkileri şekillendiren global sistemde demokrasi artık uluslararası meşruiyetin temel ölçütü haline gelmektedir. Yeni demokrasi anlayışı beraberinde yeni bir sivil toplum anlayışı getirmektedir. Küresel gelişmelerle birlikte Türkiye'nin demokratikleşme sürecinde ne kadar yol aldığı, sivil katılıma dayalı bir demokratik yönetimi ne kadar gerçekleştirebildiği konusu ise, iç ve dış faktörlere bağlı olarak geniş bir düzlemde ele alınmayı gerektirmektedir.

The issue of the impact of globalization on civil society and democratization in Turkey naturally requires a global understanding of many subjects that are subject to the process, such as political power, economic factors, social structure, evolution of the sense of democratization and poses the importance of understanding the process in a more comprehensive perspective. In this context this study discusses the major theoretical approaches to the issue of globalization and its actors within the global politics. It also reviews the global meaning of democratization and global civil society as driving force of democracy and human rights promotion strategies. As the basis of international legitimation within the globalization process, this study aims at giving an overall understanding of the international effects on building a democratic state or more democratic state, as is the case in Turkey.
Keywords: Hukuk; Kamu Hukuku; Küreselleşme; Sivil Toplum